Should Off-Label Medicines Be Included In The Universal Health Coverage (UHC) Schemes? Why, When, and How? - Ully Adhie Mulyani (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan (Journal of Research and Development in Health Services), 2017)
Abstract Off label medicine refers to any medicine that is used to treat any ailment beyond of its approved / licensed indication by National Regulatory Authorities, such us FDA in USA and BPOM in Indonesia. Off-label medicines are used because the available and approved drugs do not have the desired effect, then doctors try medicine that have not been licensed indications. Some other reasons in practice off-label medicines use and prescribing are that drugs in the same category have the same effect (although have not been approved by indication), the expansion to a lighter form than the licensed indication, or extension of use for certain related conditions. At the opposite, the disadvantage of the practice off-label medicine use is generally not included in any health insurance benefit package, also not covered by mandatory insurance scheme (JKN-BPJS). Patients should pay for the price of a drug that has not been assured or proven of its efficacy and safety. It needs strong evidence based on scientific research to ensure the safety and effectiveness of off-label medicines to be included in the list of medications (national formulary) to put it on National Health Insurance (BPJS) benefit package. Abstrak Obat off-label adalah obat yang digunakan di luar indikasi yang disetujui oleh lembaga yang berwenang, kalau di Amerika Food and Drug Administration (FDA), sedangkan di Indonesia Badan POM. Obat off label digunakan karena obat yang tersedia dan approved tidak memberikan efek yang diinginkan, sehingga dokter mencoba obat yang belum disetujui indikasinya. Beberapa alasan lain adalah adanya dugaan bahwa obat dari golongan yang sama memiliki efek yang sama (walaupun belum disetujui indikasinya), adanya perluasan ke bentuk yang lebih ringan dari indikasi yang disetujui, atau perluasan pemakaian untuk kondisi tertentu yang masih terkait. Kerugiannya adalah obat off-label umumnya tidak dicover oleh BPJS sehingga pasien harus membayar sendiri harga obat yang belum terjamin efikasi dan keamanannya. Perlu dukungan penelitian yang kuat terhadap keamanan dan efektivitas obat off label agar dapat dimasukkan dalam daftar obat (formularium nasional) yang ditanggung BPJS.